A inteligência no transtorno do espectro autista - Jeane Maria Mendes Soares (2018)
There is evidence of a high rate of occurence of Intellectual Disability in Autistic Spectrum Disorder (ASD). This evidence is questionable, once, in general, the inteligence tests, like Wechsler Intelligence Scale, assume the ability to understand and/or produce language, which is often deficient in autism. It is possible, therefore, that using these tests we are understimating these indivuals. In this regard, different groups of researchers have shown that the intelligence estimates in the population with ASD vary greatly depending on the instrument used for evaluation. In particular, these authors have argued that individuals with ASD perform better on tests that evaluate fluid intelligence than on tests that evaluate crystallized intelligence. This study had three groups of children - a group of 39 children with ASD, between 7 and 16 years old (subdivided into children with IQ less than 85 and children with IQ higher than or equal to 85), and a group of 21 children with typical development, individually paired with the participants with ASD according to age. From these groups, we examined the hypothesis that individuals with ASD have a better performance in Progressive Matrices of Raven than on the Wechsler Intelligence Scales for children - 4th edition (WISC-IV). In agreement with previous studies, in this study the participants with ASD present a better performance in the Progressive Matrices of Raven test than in the WISC-IV. The difference between the average of IQ scores reached by the Raven and WISC-IV participants for the ASD IQ group <85 was 24.65 points and for the ASD IQ group ≥85 it was 13.4, favoring the Raven test. Conversely, this difference was not observed in the control group.